2017
DOI: 10.1021/acs.biochem.7b00245
|View full text |Cite
|
Sign up to set email alerts
|

Structurally Linked Dynamics in Lactate Dehydrogenases of Evolutionarily Distinct Species

Abstract: We present new findings about how primary and secondary structure affects the role of fast protein motions in the reaction coordinates of enzymatic reactions. Using transition path sampling and committor distribution analysis, we examined the difference in the role of these fast protein motions in the reaction coordinate of lactate dehydrogenases (LDHs) of Apicomplexa organisms Plasmodium falciparum and Cryptosporidium parvum. Having evolved separately from a common malate dehydrogenase ancestor, the two enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…However, others have argued that these dynamical effects are short‐ranged (less than 6 Å) and cannot include the scaffold [5,44] . Alternatively, others suggested that the evolutionary advantage of dynamical and conformational flexibility in proteins was to accommodate different reaction mechanisms in the active site, [45,46] which enables catalytic promiscuity and facilitate the evolution of new proteins and functions [47–53] . Finally, some refer to the process by which protein dynamics influence protein activity as dynamic allostery, in analogy with allosteric regulation of protein activity upon the binding of a drug or toxin [54–56] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, others have argued that these dynamical effects are short‐ranged (less than 6 Å) and cannot include the scaffold [5,44] . Alternatively, others suggested that the evolutionary advantage of dynamical and conformational flexibility in proteins was to accommodate different reaction mechanisms in the active site, [45,46] which enables catalytic promiscuity and facilitate the evolution of new proteins and functions [47–53] . Finally, some refer to the process by which protein dynamics influence protein activity as dynamic allostery, in analogy with allosteric regulation of protein activity upon the binding of a drug or toxin [54–56] .…”
Section: Introductionmentioning
confidence: 99%
“…[5,44] Alternatively, others suggested that the evolutionary advantage of dynamical and conformational flexibility in proteins was to accommodate different reaction mechanisms in the active site, [45,46] which enables catalytic promiscuity and facilitate the evolution of new proteins and functions. [47][48][49][50][51][52][53] Finally, some refer to the process by which protein dynamics influence protein activity as dynamic allostery, in analogy with allosteric regulation of protein activity upon the binding of a drug or toxin. [54][55][56] Although all of these theories were verified convincingly for specific examples, they often focus on parts of the catalytic cycle other than the catalytic step (substrate binding, product release, catalytic promiscuity, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…They identified a conserved evolutionary motif in horse liver ADH that spans the catalytic and coenzyme binding domains (including Ser‐144, Gly‐181, Val‐203, Gly‐204, Val‐207, Glu‐267, Ile‐269, and Val‐292) and could participate in catalysis. They used transition path sampling to conclude that “protein compression” in the homologous yeast ADH “mediates a near barrier‐less hydride transfer.” They suggested that “slight changes in promoting vibrations (in lactate dehydrogenase) result in dramatic changes in enzyme chemistry.” The contribution of such fast dynamics to catalysis of hydride transfer by ADH needs experimental evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…52,53 They suggested that "slight changes in promoting vibrations (in lactate dehydrogenase) result in dramatic changes in enzyme chemistry." 54,55 The contribution of such fast dynamics to catalysis of hydride transfer by ADH needs experimental evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Significant effort has been directed to understanding the mechanism of enzymatic catalysis. Increasing evidence has shown that dynamic motions of enzymes play an important role in catalytic process. Recent theoretical and experimental studies have shown that sub-picosecond motions, which are on the same time scale as the chemical step of enzymatic reactions, can couple with the reaction coordinate of enzymes. ,,, These femtosecond motions are termed rate promoting vibrations (RPVs), since couplings between these motions and reaction coordinates can promote the rate of the chemical step in the reaction process. The RPV promotes the rate of the chemical step of an enzymatic reaction by dynamically modulating the height and width of the potential energy barrier .…”
mentioning
confidence: 99%